IMAGING CHARACTERISTICS OF CLOSED SCAPULAR FRACTURES ON RADIOGRAPHY AND COMPUTED TOMOGRAPHY (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the morphological characteristics of closed scapular fractures on radiography and CT, and to evaluate the diagnostic value of radiography compared with CT in detecting scapular fractures and associated thoracic injuries.Subjects and methods: A retrospective-prospective descriptive study was conducted on 220 patients with closed scapular fractures diagnosed and treated at the hospital. All patients underwent plain radiography and chest CT or shoulder CT. Epidemiological characteristics, injury mechanisms, fracture locations, number of fracture fragments, AO/OTA classification, and associated thoracic injuries were analyzed and compared between the two imaging modalities.Results: The mean age of patients was 48.9 ± 15.2 years, with males accounting for 84.1%. Traffic accidents were the most common cause of injury (70%). Radiography detected 70.5% of scapular fractures, whereas 29.5% of cases were missed and only identified on CT. The sensitivity of radiography varied depending on fracture location: 69.4% for scapular body fractures, 66.7% for glenoid fractures, 35.3% for acromion fractures, 26.1% for coracoid fractures, and 0% for scapular spine fractures. CT detected three or more fracture fragments significantly more frequently than radiography (56.4% vs. 28.4%; p = 0.007). AO/OTA classification based on CT also revealed a higher proportion of complex fracture patterns compared with radiography. Furthermore, CT identified significantly more associated thoracic injuries than radiography, particularly pulmonary contusion, hemothorax, and pneumothorax (p < 0.01).Conclusion: Plain radiography plays an initial role in the detection of scapular fractures; however, its sensitivity is limited and complex fracture patterns are frequently missed, especially in fractures involving the coracoid process, acromion, and scapular spine. CT provides superior diagnostic accuracy in evaluating fracture morphology and detecting associated thoracic injuries; therefore, it should be routinely indicated when scapular fracture is suspected.
Keywords: Scapular fracture, CT scan, X-ray, AO/OTA classification, thoracic trauma.